The teacher who goes the extra (s)mile: a study among primary school teachers in Namibia (Journal for Studies in Humanities and Social Sciences, 2016)
This study focused on job factors (work engagement, organisational commitment) and psychological states (psychological availability, meaningfulness, autonomy, psychological safety) that teachers (N = 628) in Namibian primary schools need for increased organisational citizenship behaviour (OCB). OCB indicates a teacher’s spontaneous willingness to perform work that is over and above the work description. A quantitative research design with a field survey has been used with a non-random convenience sample of teachers in all regions of Namibia. Measuring instruments used, were: Work Engagement Scale, Organisational Commitment Scale, Psychological Conditions Scale, Organisational Citizenship Behaviour Scale and a biographical questionnaire. Initial statistical analysis included exploratory factor analysis and confirming the reliability of the scales. In addition, descriptive statistics, Pearson correlations and multiple hierarchical regression analyses were conducted. Mean scores indicated lower levels of cognitive engagement, autonomy, psychological safety and OCB. Medium correlations were found between job factors and OCB as well as between organisational commitment and OCB and psychological conditions and OCB. Other main fi ndings indicated that work engagement (especially physical engagement), organisational commitment as well as the psychological states autonomy and psychological availability were the more significant predictors of OCB. Contrary to expectations, the psychological states of meaningfulness and safety did not significantly predict OCB. Relevant recommendations were formulated based on the results of this study.